Radial artery neointimal hyperplasia after transradial PCI-Serial optical coherence tomography volumetric study - Kala, Petr; Kanovsky, Jan; Novakova, Tereza; Miklik, Roman; Bocek, Otakar; Poloczek, Martin; Jerabek, Petr; Prymkova, Lenka; Ondrus, Tomas; Jarkovsky, Jiri; Blaha, Milan; Mintz, Gary S (PloS one, 2017)
AIMS: Transradial catheterization (TRC) is a dominant access site for coronary catheterization and percutaneous coronary interventions (PCI) in many centers. Previous studies reported higher intimal thickness of the radial artery (RA) wall in patients with a previous history of TRC. In this investigation the aim was to assess the intimal changes of RA using the optical coherence tomography (OCT) intravascular imaging in a serial manner. METHODS AND RESULTS: 100 patients with the diagnosis of non-ST-elevation myocardial infarction (nSTEMI) treated by PCI were enrolled (6 patients were excluded from this analysis because of occluded RA at follow-up [2 patients] and insufficient quality of OCT images [4 patients]). An 54mm long OCT run of the RA was performed immediately after the index PCI and repeated 9 months later. Volumetric analyses of the intimal layer and lumen changes were conducted. Median intimal volume at baseline versus 9 months was 33.9mm3 (19.0; 69.4) versus 39.0mm3 (21.7; 72.6) (p<0.001); and median arterial lumen volume was 356.3mm3 (227.8; 645.3) versus 304.7mm3 (186.1; 582.7) (p<0.001). There was no significant difference in the effect of any clinical factor on the RA volume changes. CONCLUSIONS: OCT volumetric analyses at baseline and 9 months showed a significant increase in the radial artery intimal layer volume and a decrease in lumen volume after transradial PCI. No significant factors affecting this process were identified.
Keywords: senioři; neointima; Hyperplasia; senioři nad 80 let; srdeční katetrizace; Cardiac Catheterization; Middle Aged; tunica intima; mužské pohlaví; infarkt myokardu; arteria radialis; Neointima; koronární angiografie; Myocardial Infarction; Coronary Angiography; Aged, 80 and over; Radial Artery; ženské pohlaví; optická koherentní tomografie; Humans; hyperplazie; Tomography, Optical Coherence; koronární angioplastika; lidé středního věku; Percutaneous Coronary Intervention; Tunica Intima; Female; Aged; lidé; Male